Coevolution of cooperation, preferences, and cooperative signals in social dilemmas - Stephan Müller; Georg von Wangenheim (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
We study the coevolution of cooperation, preferences, and cooperative signals in an environment where individuals engage in a signaling-extended prisoner's dilemma. We prove the existence of a cooperative equilibrium constituted by a (set of) limit cycle(s) and stabilized by the dynamic interaction of multiple Bayesian equilibria. This equilibrium: (1) exists under mild conditions, and (2) can stabilize a population that is characterized by the heterogeneity of behavior, preferences, and signaling. We thereby offer an explanation for the persistent regularities observed in laboratory and field data on cooperative behavior. The cyclicity of the equilibrium offers an alternative account for observed historical changes in (social norms of) cooperation in societies which are not driven by social or environmental shocks.
Keywords: C73; D64; D82; 330; evolutionary game theory; cooperation; preferences; signaling